PENYULUHAN STUNTING UNTUK PENINGKATAN PENGETAHUAN SISWA/SISWI MAN INDRAPURI ACEH BESAR - Lensoni; Andriaty, Syarifah Nora; Zahara, Hafni; Kala, Pasyamei Rumbune; Anggriani, Yayu; Raisah, Putri; Karma, Taufik; Yanti, Murni; Ajaratudur; Merisa (Transpublika Publisher, 2022)
The problem of stunting is one of the nutritional problems faced in the world, especially in poor and developing countries. Stunting is a form of growth failure (growth faltering) due to the accumulation of nutritional inadequacy that lasts for a long time starting from pregnancy until the age of 24 months. The population in this study were teenagers/students of Man Indrapuri. The sampling technique used is total sampling. In the study, the independent variable was the provision of counseling about stunting, while the dependent variable was the knowledge of the students of Man Indrapuri I Aceh Besar. The number of samples taken was 20 students. Based on the results of the study, where after counseling the knowledge of students about stunting increased from before being given counseling. Where the percentage before counseling is as much as 40% to 90% after counseling. If there is an increase in respondents after counseling, it can be said that the provision of education with the extension method is very effective for students' knowledge about stunting so that it can reduce the risk of stunting cases in the community.